Iridium-Catalyzed C-3 Allylation of Indoles with Allylic Alcohols Promoted by a Brønsted Acid - Chen, Shu-jie; Lu, Guo-ping; Cai, Chun (Synthesis, 2014)
A highly regioselective method has been developed for the allylation of indoles with an iridium catalyst. This regioselective procedure uses allylic alcohols directly as allylating agents in the presence of a catalytic amount of sulfuric acid. A wide range of indoles reacted smoothly with asymmetrical allylic alcohols to give the corresponding branched products in branched-to-linear ratios of up to 99:1 and yields as high as 92%. A series of inorganic and organic acids were tested in this approach, and it was shown that acids with pKa values in acetonitrile of less than 15 are required in this iridium-catalyzed system.
Keywords: iridium; allylations; indoles; regioselectivity; homogeneous catalysis